Measuring the imaginary-time dynamics of quantum materials. Issue 19 (1st October 2020) - Lederer, S.; Jost, D.; Böhm, T.; Hackl, R.; Berg, E.; Kivelson, S. A.
ABSTRACT: Theoretical analysis typically involves imaginary-time correlation functions. Inferring real-time dynamical response functions from this information is notoriously difficult. However, as we articulate here, it is straightforward to compute imaginary-time correlators from the measured frequency dependence of (real-time) response functions. In addition to facilitating comparison between theory and experiment, the proposed approach can be useful in extracting certain aspects of the (long-time relaxational) dynamics from a complex data set. We illustrate this with an analysis of the nematic response inferred from Raman scattering spectroscopy on the iron-based superconductor B a ( F e 1 − x C o x ) 2 A s 2, which includes a new method for identifying a putative quantum-critical contribution to that response.